ACTIVATION OF THE POETIC WORD IN SPEECH (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
It is known that language is a complex and at the same time creative system. Speech, which is the emergence and realization of language, is also a device that has its own boundless creativity, manifesting the capabilities of language in a form appropriate to speech conditions. Having the mutual associative property is not exactly the same in language and speech. Linguistic units, such as lexemes, have paradigmatic, syntagmatic, and sometimes hierarchical relationships that always point to and resemble each other. A pronounced polysemantic word with each meaning creates a separate circle, and they become lexemes and occupy a place in certain paradigms of the language. This phenomenon in most cases is associated with the use of the word in a figurative sense.This article brings to the linguapoetic analysis the peculiarity of the figurative use of some words in the poems of the famous Uzbek poetess Halima Khudoiberdieva.